Dillinger's wild ride : the year that made America's public enemy number one - Gorn, Elliott J., 1951- (Oxford Univ. Press, 2009)
In an era that witnessed the rise of celebrity outlaws like Baby Face Nelson, Pretty Boy Floyd, and Bonnie and Clyde, John Dillinger was the most famous and flamboyant of them all. Reports on the man and his misdeeds--spiced with accounts of his swashbuckling bravado and cool daring--provided an America worn down by the Great Depression with a salacious mix of sex and violence that proved irresistible. In Dillinger's Wild Ride, Elliott J. Gorn provides a riveting account of the year between 1933 and 1934, when the Dillinger gang pulled over a dozen bank jobs, and stole hundreds of thousands of dollars.